BEACH SOCCER HISTORIES - McGowan, Lee. ([S.l.])
1 online resource
Keywords: Beach Soccer Histories is the first text to consider the sport as a historical, social and cultural phenomenon, to define its traditions, and present leading research on the development and significance of football played on sand. Following a period of expansive, rapid growth, beach soccer is an internationally governed professional sport, which has come a long way from its origins in Rio de Janeiro in the 1920s. The sand-based variant is distinguished from football by a range of factors, including the dramatic impact of the playing surface. Yet, the game has undergone very little academic scrutiny. This research adopts and adapts qualitative methods related to oral history and football studies, including extensive archival research, semi-structured interviews, and textual and thematic analyses. As it looks beneath the game's contemporary reach, it considers origins, organisations - including FIFA's influence - and the beach cultures that underpin its sporting and historical development. This the most comprehensive exploration of beach soccer and a century of its existence. Beach Soccer Histories examines the game's historical development, critical moments and movements in its progress, successes and contentions, and its contemporary state of play with a view to deepening and advancing our understanding of the game.